ANALYSIS OF IB MUAMALAT PRIMA BISNIS SAVINGS PRODUCTS ON THE REAL ECONOMIC SECTOR OF THE COMMUNITY (CASE STUDY OF PT. BANK MUAMALAT INDONESIA, TBK BANJARMASIN BRANCH) - Purnomo, Agus; Rusdiansyah, Muhammad (Universitas Airlangga, 2019)
This research is motivated by the researcher who previously conducted the Work Practice in PT.Bank Muamalat Indonesia, Tbk Branch Banjarmasin Years 2016 as Marketing Funding. After knowing the superior Funding Product of Bank Muamalat Indonesia Branch of Banjarmasin ie iB Muamalat Prima Business Savings. The reasercher tries to find out the influence of this Product in addition to beneficial to the Customer but the perceived impact in driving the Customer Business That's where it is. The purpose of this research was undertaken by Benefits of Savings Products iB Muamalat Prima Business as a whole and to determine the effect of Savings Products iB Muamalat Prima Business Against the Rill Sector Field SMEs (Micro Small and Medium Enterprises) community. This research used Qualitative method descriptive qualitative approach. The data obtained then in the form of data information such as observation, interviews, field notes and documentation. For Respondent data source counted to 3 people namely Business Development Manager Funding, Marketing Funding and Customer Service. While informants counted to 5 people namely the Customer Savings Product iB Muamalat Prima Bussiness as entrepreneurs and not entrepreneurs. The results of this research indicate that there is a great influence in mobilizing the Rill Sector of the Economic Community, depending on the Customer itself willing to be used as a transactional tool with business partners or as a Product User Customer.Keywords : Savings Products, Rill Sector, Economy Public.